2021
DOI: 10.1128/msphere.00267-21
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Venom Antimicrobial Peptides Induce Siderophore Biosynthesis and Oxidative Stress Responses in Escherichia coli

Abstract: The increasing development of microbial resistance to classical antimicrobial agents has led to the search for novel antimicrobials. Antimicrobial peptides (AMPs) derived from scorpion and snake venoms offer an attractive source for the development of novel therapeutics. Smp24 (24 amino acids [aa]) and Smp43 (43 aa) are broad-spectrum AMPs that have been identified from the venom gland of the Egyptian scorpion Scorpio maurus palmatus and subsequently characterized. Using a DNA microarray approach, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…38 Hierarchical clustering was used to group the strain samples, and the dendrogram is displayed at the top of a heatmap that shows the Pearson correlation between each pair of samples. 39 Sample identity was shown by two-way color indexing the group and strain. The results demonstrated that KP and PA samples from different groups and strains could be successfully distinguished.…”
Section: Data Normalizationmentioning
confidence: 99%
“…38 Hierarchical clustering was used to group the strain samples, and the dendrogram is displayed at the top of a heatmap that shows the Pearson correlation between each pair of samples. 39 Sample identity was shown by two-way color indexing the group and strain. The results demonstrated that KP and PA samples from different groups and strains could be successfully distinguished.…”
Section: Data Normalizationmentioning
confidence: 99%
“…Furthermore, some AMPs can target intracellular components such as nucleic acid and proteins. It has been reported that AMPs Smp24 and Smp43 from the Egyptian scorpion Scorpio maurus palmatus not only disrupt bacterial cell membranes but can also interfere with intracellular gene expression ( Tawfik et al, 2021 ). A study using radioactive isotopes clearly showed that I9K-IsCT and E7K, which are analogs of IsCT from the scorpion O. madagascariensis , inhibit nucleic acids and protein synthesis in E. coli ( Tripathi et al, 2015 ).…”
Section: General Antimicrobial Peptide Molecular Targetsmentioning
confidence: 99%
“…One group of these new molecules are peptides that are antimicrobial (AMP) and are promising molecules for combating antimicrobial resistance (AMR) [ 28 ]. AMP has been found the most in the venoms of different organisms, such as scorpions [ 29 , 30 , 31 ], snakes [ 32 ], spiders [ 33 ], and bees [ 34 ], among other venoms.…”
Section: Introductionmentioning
confidence: 99%